The Koran in the Works of A.S. Pushkin - Djumaeva, Sh.Ch.; Bakhtiyarovna, Khushbokova Shakhzoda (European Journal of Life Safety and Stability (2660-9630), 2023)
This article tells how A. S. Pushkin knew the Koran well and he drew it as a work of great and very peculiar artistic power, as a wonderful example of oriental poetry... The poet used the Koran in his works as courageous truthfulness, contempt for deceit and hypocrisy, people’s belief in the One God and the attitude of the Creator to his perfect creations.